1981
DOI: 10.3758/bf03197562
|View full text |Cite
|
Sign up to set email alerts
|

The role of memory in the construction of linear orderings

Abstract: Two experiments examined the construction of linear orderings (e.g., ABCD) from presented pairs of adjacent items (e.g., AB, BC, CD) in an attempt to determine why some orders of presentation are more difficult than others. Experiment 1 found order effects when participants constructed orderings but not when they simply recalled presented pairs, suggesting that order effects reflect processing difficulties encountered during construction. Experiment 2 used several different orders and successive and simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…In sum , the present results support the hypothesis (Foos & Sabol, 1981) that differences between match and nonmatch presentation orders are due primarily to memory load , whereas other order effects are due primarily to processing differences . In addition , the results suggest that, under conditions of increased memory load , individuals find it easier to construct in a single direction (beginning or end) and more difficult to construct in two directions (beginning and end ).…”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations
“…In sum , the present results support the hypothesis (Foos & Sabol, 1981) that differences between match and nonmatch presentation orders are due primarily to memory load , whereas other order effects are due primarily to processing differences . In addition , the results suggest that, under conditions of increased memory load , individuals find it easier to construct in a single direction (beginning or end) and more difficult to construct in two directions (beginning and end ).…”
Section: Methodssupporting
confidence: 79%
“…The other differences described above are due primarily to processing. Studies that have reduced memory load (Foos & Clark, 1983;Foos & Sabol, 1981) have shown that such reductions reduce matchnonmatch differences but do not significantly alter the other differences assumed to be due to processing. The present study attempted to address this question by increasing, rather than reducing, memory load.…”
Section: The Construction Of Linear Orderings Under Conditions Of Incmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, Baker compared the mean of the chronological sequence (1-2-3) with the means of the two flashback sequences (1-3-2 and 2-1-3), but, as mentioned previously, the 1-3-2 flashback sequence should have been no more difficult than the chronological sequence if the information remained available (Foos & Sabol, 1981). A comparison of the subject's performance for the chronological sequence (1-2-3) with that for the diacult flashback sequence (2-1-3) might have demonstrated an effect of input sequence on story-reading time.…”
mentioning
confidence: 98%